Acute disseminated encephalomyelitis in a SARS-CoV2 seropositive child - Pankaj Sahu; Ritu (Indian Journal of Child Health, 2021)
Children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have various clinical presentations. Neurological manifestations of SARS-CoV-2 have been described in adults but such presentations in children are rare. The different neurological manifestations associated with SARS-CoV-2 are headache, seizures, anosmia, ischemic stroke, encephalopathy, transverse myelitis, and Guillain-Barre Syndrome. Here, we describe a case of SARS-CoV-2 seropositive child presenting as acute disseminated encephalomyelitis.